TINGKAT KEPUASAN MASYARAKAT TERHADAP PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA KELURAHAN KETINTANG KOTA SURABAYA - Selvia, Yusniati; Isbandono, Prasetyo (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The increase in the value of IKM for public services in the Ketintang Village, but the reality in the field of service has not met the expectations of the community, due to the facilities and infrastructure that have not been maximized, such as the lack of chairs in the waiting room and the waiting room is not equipped with air conditioning. This type of research is a quantitative descriptive method, measured based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017 concerning Guidelines for Compiling a Community Satisfaction Survey, with a population of 150 people and a sample of 60 respondents. The results of research on population administration services in the Ketintang Village of Surabaya City based on calculations using nine elements obtained seven elements with categorization B "Good" namely: requirements; systems, mechanisms, and procedures; turnaround time; product specification type of service; executor competency; executor behavior; handling, complaints, suggestions and feedback. In addition, the highest IKM score is at the cost (tariff) with an elemental value of 4.00 or an IKM value of 100 and categorized A "Very Good", while the lowest IKM score is facilities and infrastructure with an elemental value of 2.67 or an IKM value of 66 .67 and categorized C "Enough". However, the overall value of IKM population administration services in Ketintang Village, Surabaya City is 81.37 or categorized B "Good". Keywords: Community Satisfaction, Population Administration Services